PENGARUH MOTIVASI DAN MENTAL BERWIRAUSAHA TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK BERWIRAUSAHA STUDI PADA MAHASISWA UNIVERSITAS AHMAD DAHLAN - Agung, Alvian Dhian; Sumaryanto, Sumaryanto (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2015)
Effect of entrepreneurship education has been considered as one of the important factors to grow and develop interest in entrepreneurship among students. With the influence of entrepreneurship education, required an understanding of how to foster young entrepreneur potential while still in college. Several previous studies mention that the student interest in entrepreneurship is the source for the birth of future entrepreneurs. The researchers using purposive sampling. The samples used in this study were 45 students majoring in Accounting active in the UAD (Ahmad Dahlan University), class of 2009 who have followed the entrepreneurship courses given, and active semester 2013/2014. Source of data obtained from questionnaires, and then analyzed using analysis techniques using multiple linear analysis techniques and tested with the F test and t test. From the test results we concluded that the resulting regression analysis to determine the effect of motivation on student interest in accounting for entrepreneurship, and entrepreneurship does not affect the mental accounting student interest in UAD for entrepreneurship.